The effect of self-care, self-efficacy, and health literacy on health-related quality of life in patients with hypertension: a cross-sectional study - Nastaran Salmanpour; Alireza Salehi; Sadaf Nemati; Mahdi Rahmanian; Alireza Zakeri; Hamed Bazrafshan drissi; Mohammad Reza Shadzi (BMC Public Health)
Abstract Background Hypertension is a common chronic disease that negatively affects health-related quality of life (HRQOL). Identifying modifiable factors influencing HRQOL is essential to improve patient outcomes. This study focuses on self-care, self-efficacy, and health literacy due to their established role in chronic disease management and their potential to be enhanced through targeted interventions. These variables were selected based on Social Cognitive Theory and the Health Literacy Skills Framework, which highlight the roles of self-efficacy and health literacy in promoting effective self-care and improving health outcomes. Methods In this cross-sectional study, data on HRQOL, self-care, self-efficacy, and health literacy were collected from 427 patients selected through systematic random sampling between March 2023 and March 2024 in community and private sector clinics affiliated with Shiraz University of Medical Sciences, Shiraz, Iran. Data were obtained via interviews using validated questionnaires, including WHOQOL-BREF, Hill-Bone, HBP-SCP, and HELIA-SF, along with patients’ demographic, anthropometric, and physiological information. A multiple linear regression model was used for data analysis. Additionally, logistic regression was performed to estimate odds ratios (ORs) for categorized HRQOL outcomes. Results The mean (SD) age of participants was 60.1 (11.1) years, with the majority (68.4%) being women. The mean (SD) scores for total HRQOL, self-care, self-efficacy, and health literacy were 62.5 (15.8), 87.1 (10.8), 68.7 (14.9), and 81.2 (17.2), respectively. Bivariate analysis revealed that male gender (p = 0.009), being employed (p < 0.001), and having a higher income (p < 0.001) were significantly associated with better HRQOL, whereas participants with diabetes mellitus (p = 0.001) and renal disease (p = 0.002) exhibited reduced considerably HRQOL. In the linear regression model, better self-care (β = − 0.34, 95% CI: − 0.67 to 0.00), higher self-efficacy (β = 0.28, 95% CI: 0.10–0.45), and greater health literacy (β = 0.37, 95% CI: 0.29–0.44) were significantly associated with higher HRQOL scores. Effect sizes were small for self-care (η² = 0.02), moderate for self-efficacy (η² = 0.03), and large for health literacy (η² = 0.13). Presence of diabetes (β = 3.8, 95% CI: 1.1–6.5) and renal disease (β = 3.2, 95% CI: 0.08–6.3) was significantly linked to lower HRQOL scores, though effect sizes were minimal (η² = 0.005 and 0.003). In the logistic regression model, higher self-efficacy (OR = 1.05, 95% CI: 1.01–1.08) and health literacy (OR = 1.04, 95% CI: 1.03–1.06) were associated with greater odds of reporting good HRQOL. Absence of diabetes (OR = 1.57) and renal disease (OR = 1.34) was also favorably associated with HRQOL. Gender and education were not significant predictors. Conclusion Although health literacy, self-care, and self-efficacy are associated with HRQOL in patients with hypertension, only health literacy demonstrated a sizeable effect size. Therefore, interventions aimed at enhancing these factors, particularly health literacy, should be prioritized in public health strategies to improve the quality of life in this population.